2014
DOI: 10.5935/1678-9741.20140044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of variables responsible for hospital mortality in patients with rheumatic heart disease undergoing double valve replacement

Abstract: ObjectiveTo describe the hospital mortality and associated clinical and echocardiographic variables in patients with rheumatic disease who underwent double valve replacement surgery.MethodsThis is a cross sectional descriptive study of mortality, performed in a referral hospital in Salvador, Bahia. Records from patients with rheumatic disease who underwent double valve replacement surgery during the years 2007-2011 were analyzed.ResultsThe studied sample comprises 104 patients and 60 (57.7%) were male. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
3
6
1
1
Order By: Relevance
“…While some studies have not demonstrated an association between atrial fibrillation and unfavorable outcomes, 32,34 as described in this article, others have shown that it is a risk factor. 16,19,27,29,31,35 We did not find any relationship between any other preoperative variable (diagnoses or laboratory findings) and higher mortality, which is in line with results reported by Fernandes et al 28 and De Bacco et al 32 However, previous publications have reported an association of elevated BMI values, 10,26 history of coronary artery disease, 16,22,30,33 endocarditis, 22 stroke 30 , hypertension and COPD 19 with postoperative complications and death. Among laboratory variables, elevations in creatinine / kidney injury 17,19,22,32 and reduced hemoglobin and hematocrit values 28 have already been reported as risk factors, which was not observed in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While some studies have not demonstrated an association between atrial fibrillation and unfavorable outcomes, 32,34 as described in this article, others have shown that it is a risk factor. 16,19,27,29,31,35 We did not find any relationship between any other preoperative variable (diagnoses or laboratory findings) and higher mortality, which is in line with results reported by Fernandes et al 28 and De Bacco et al 32 However, previous publications have reported an association of elevated BMI values, 10,26 history of coronary artery disease, 16,22,30,33 endocarditis, 22 stroke 30 , hypertension and COPD 19 with postoperative complications and death. Among laboratory variables, elevations in creatinine / kidney injury 17,19,22,32 and reduced hemoglobin and hematocrit values 28 have already been reported as risk factors, which was not observed in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Age, for example, has already been associated with higher mortality in several studies, as well as in ours. 3,10,12,16,22,[28][29][30][31] . However, this is still not a consensus, since others have found no difference between groups, 25,32 or even an inverse relationship.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Patients with RHD have valvular lesion caused by the rheumatic valve involvement (stenosis and/or regurgitation) or secondary to ventricular dilatation, leading to mitral or tricuspid insufficiency. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Multiple valve involvement with progressive stenosis usually occurs late in the disease course, either due to rheumatic involvement or subsequent dilation. In patients undergoing double valve replacement, it was noted that NYHA status and hemoglobin levels were successful predictors of surgical outcome [8]. Both were significantly compromised in this patient due to her aforementioned comorbidities.…”
Section: Introductionmentioning
confidence: 73%
“…Severe biatrial dilatation can predispose the patient to malignant arrhythmias and thromboembolism, not to mention challenges in sternotomy, surgical exposure, and cannulation [8].The selection of vasopressor/inotropes had to be carefully titrated, given the patient's multiple cardiac pathologies affecting loading conditions and function, with additional supplementation of amiodarone due to high likelihood of postoperative arrythmia.…”
Section: Introductionmentioning
confidence: 99%